The widening of inequalities in a tourist destination as a result of the global crisis - Gauna, Carlos; Vargas, Rosa (Revista Española de Desarrollo y Cooperación, 2023)
Tourism is sensitive to changes in the economy, the effects generated by the Great Recession of 2008 were immediately manifested; consumers, in an attitude of caution before the possible losses protected themselves not making dispensable purchases (such as tourism) while stability was recovered, which caused damages to destinations that were transferred to vulnerable groups, expanding inequalities.